Analisis Informasi Anatomi Pemeriksaan MRI Ankle Joint pada Penggunaan Foot Ankle Coil dan Flex Coil Proton Density Fat Saturation Irisan Sagital - Kartikasari, Yeti; Kurniawan, Andrey Nino; Hidayat, Subhan Syarif (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: To get good MRI image quality, a special coil is designed according to the type of examination with various types and sizes so that it can be adjusted to the body to be examined so that the selection of coil is very important in MRI examination. At Dr.R.Soeharso Surakarta Orthopedi Hospital, it was found on an MRI examination of the  ankle joint using a foot ankle  coil and also sometimes also using a flex coil. The purpose of this study was to determine the difference in anatomical information of ankle joint MRI examination on Proton Density Fat Saturation Sagittal Slices using foot ankle coil and flex coil.   Methods: This research is quantitative research with an experimental approach. This research was conducted on 10 volunteers. Respondents assessed image information on the anatomy of the Achilles tendon, talocalcaneal ligament, tibiofibular ligament, talofibular ligament, talotibial ligament, tenton flexor digitorum, extensor digitorum tendon, os calcaneus, os tallus, os tibia. Results: Ten probandus were performed MRI examination of ankle joint, proton density weighting, sagittal slice using foot ankle coil and flex coil. Images are produced that can show predetermined anatomical information, namely: Achilles tendon, talocalcaneal ligament, tibiofibular ligament, talofibular ligament, talotibial ligament, tenton flexor digitorum, extensor digitorum tendon, os calcaneus, os tallus, os tibia. Based on Wilcoxon's nonparametric statistical test in table shows that the resulting p value is 0.001 (p-value is <0.05) which means that there is a significant difference in the overall anatomical information of ankle joint MRI examination on the use of foot ankle coil and flex coil proton density fat saturation sagittal slices and mean rank results (28.50) foot ankle coil (0,001) flex coil.Conclusions: The anatomical information produced in the use of foot ankle coil is better than the anatomical information produced by flex coil on MRI examination of ankle joint proton density fat saturation sagittal slice.